High risk of osteoporosis and fracture following solid organ transplantation: a population-based study - Chen, Hsin; Lai, Yung-Rung; Yang, Yih; Gau, Shuo-Yan; Huang, Cheng-Yang; Tsai, Tung-Han; Huang, Kuang-Hua; Lee, Chien-Ying (Frontiers in Endocrinology, 2023)
Background Osteoporosis and fractures increase morbidity and mortality rates after solid organ transplantation (SOT), but few studies have analyzed the risk of osteoporosis and related fractures after SOT. In this retrospective cohort study, we investigated the risk of osteoporosis and fractures in different SOT recipients. Methods This study was a retrospective cohort study by using a nationally representative database in Taiwan, we collected the data of SOT recipients and used the propensity score matching method to obtain a comparison cohort. To reduce bias, we excluded the patients who had been diagnosed with osteoporosis or fracture before inclusion. All participants were follow-up until the date of diagnosed as having pathological fracture, death, or the end of 2018, whichever occurred first. The Cox proportional hazards model was used to investigate the risk of osteoporosis and pathological fracture in SOT recipients. Results After adjustment for the aforementioned variables, SOT recipients were observed to have a higher risk of osteoporosis (hazard ratio, HR = 1.46, 95% confidence interval, CI: 1.29-1.65) and fracture (HR: 1.19, 95% CI: 1.01-1.39) than the general individuals. Among the different SOT recipients, the highest risk of fractures was noted in heart or lung transplant recipients, HR: 4.62 (95% CI: 2.05-10.44). Among the age groups, patients aged >61 years had the highest HRs for osteoporosis (HR: 11.51; 95% CI, 9.10-14.56) and fracture (HR: 11.75, 95% CI: 8.97-15.40). Conclusion SOT recipients had a higher risk of osteoporosis and related fractures than the general population, with the highest risks observed in patients receiving heart or lung transplant, older patients, and patients with CCI score >3.